Apicectomia e curetagem apical: relato de caso. - (:unkn) unknown (Universidade Brasil, 2024)
Endodontic treatment failure can be identified through clinical and radiographic evaluations, with symptoms such as spontaneous pain, sensitivity to palpation, vertical percussion pain, swelling, and the presence of periapical lesions. When these signs are detected, endodontic retreatment is usually the first approach; however, if this option is not feasible, periapical surgery may be recommended. The literature describes several techniques for these cases, including periapical curettage, apicoectomy, surgery with retrograde obturation, and retro-instrumentation with retro-obturation. The aim of this study is to report the case of a 41-year-old female patient who sought dental care due to the emergence of an intraoral fistula. After clinical and radiographic examinations, she was diagnosed with chronic periapical abscess in tooth 12. In the first consultation, a coronal access was performed, and root canal instrumentation was carried out up to the apical third, followed by intracanal medication with Ultracal for 15 days. In the second consultation, the persistence of the fistula led to the re-opening of the canal, re-instrumentation, and substitution of the medication, which remained for 30 days. In the third consultation, the regression of the fistula was noted, and the canal was obturated with Sealapex cement. However, after 30 days, the patient returned with the reappearance of the fistula. Given this scenario, periapical surgery was indicated and scheduled, including apicoectomy of the apical third and curettage of the endodontic lesion. Following the procedure, the patient did not report pain upon apical palpation, sensitivity to vertical percussion, spontaneous pain, or recurrence of the fistula during the 7-month postoperative follow-up. conclusion: When conventional endodontic treatment methods are not applicable or complications occur during the procedure, periapical surgery proves to be an effective alternative to preserve the tooth, restoring health, aesthetics, and function to the patient.
Keywords: Apicectomia; Endodontia; Tratamento do canal radicular; Saúde